Development of adaptive parametric interface for analytical queries: electrical equipment management system case study - Orlovskyi, D. L.; Kopp, A. M.; Bilous, I. S. (Одеська національна академія харчових технологій, 2020)
This paper considers the case study of the development of adaptive parametric interface for analytical queries in an electrical equipment management system. The relevance of information technology usage in a power engineering industry is considered, as well as the related studies in the field of query form generation for information systems are analyzed. The set of query form parameters is defined and example of such form is demonstrated. Formalized query form features could be used to gather the most preferable configurations and develop a recommender module in order to improve the user experience.
Keywords: adaptive parametric interface; electrical equipment management; information technology; power engineering